Study of heat treatment effect on the biological value of pine nuts kernels - Mykhalevych, Artur; Bandura (Kuzmyk), Uliana (My University, 2022)
The aim of the research was to determine the optimal modes of heat treatment of pine nut kernels in order to preserve their biological value to the optimal, which will allow in the future to use this type of raw material in the technology of various types of sauces with the addition of dry whey. The article analyzes the drying kinetics of Pinus pinea Linneus pine nut kernels for 120 minutes under 4 heat treatment regimes: 20, 40, 60 and 80 ˚C. The effect of heat treatment on the composition of essential amino acids, the content of vitamin C and β-carotene was studied. Thus, the temperature of 20 and 40 ˚C ensures the maximum preservation of the biological value of the raw material, but it does not allow to achieve a significant decrease in the mass fraction of moisture, which will negatively affect the microbiological indicators of the raw material. During processing at 60 ˚С, the mass fraction of moisture in the kernels of pine nuts decreases from 7 to 5.28 %, which is likely to reduce water activity and positively affect the duration of storage. An increase in temperature to 80 ˚С significantly reduces the content of essential amino acids and β-carotene, as well as makes it impossible to achieve a technological effect (a significant decrease in moisture content) with the irrational use of energy resources. It was established that the optimal mode of heat treatment of pine nut kernels is drying at a temperature of 60 ˚С, which ensures the preservation of the biological value of the raw material and meets the recommendations for achieving satisfactory microbiological indicators. Метою дослідження було визначення оптимальних режимів термічної обробки ядер кедрових горіхів з метою оптимального збереження їх біологічної цінності, що дозволить у майбутньому використовувати даний вид сировини в технології різних видів соусів з додаванням сухої сироватки. У статті проаналізовано кінетику сушіння ядер кедрового горіха Pinus pinea Linneus протягом 120 хвилин за 4 режимів термічної обробки: 20, 40, 60 і 80 ˚C. Вивчено вплив термічної обробки на склад незамінних амінокислот, вміст вітаміну С і β-каротину. Таким чином, температура 20 і 40 ˚C забезпечує максимальне збереження біологічної цінності сировини, але не дозволяє досягти значного зниження масової частки вологи, що негативно позначиться на впливають на мікробіологічні показники сировини. При обробці при 60 ˚С масова частка вологи в ядрах кедрових горіхів зменшується з 7 до 5,28 %, що, ймовірно, знижує активність води та позитивно впливає на тривалість зберігання. Підвищення температури до 80 ˚С істотно знижує вміст незамінних амінокислот і β-каротину, а також унеможливлює досягнення технологічного ефекту (значне зниження вологості) при нераціональному використанні енергетичних ресурсів. Встановлено, що оптимальним режимом теплової обробки ядер кедрового горіха є сушіння при температурі 60 ˚С, що забезпечує збереження біологічної цінності сировини та відповідає рекомендаціям щодо досягнення задовільних мікробіологічних показників.
Keywords: drying kinetics; moisture content; amino acid composition; β-carotene; vitamin C; pine nut kernels; кафедра технології молока і молочних продуктів; кінетика сушіння; вологовміст; амінокислотний склад; бета-каротин; вітамін С